EOGT Correlated With Immune Infiltration: A Candidate Prognostic Biomarker for Hepatocellular Carcinoma - Shu, Yang; He, Lingling; Gao, Meixin; Xiao, Fan; Yang, Junru; Wang, Shiwei; Wei, Herui; Zhang, Fuyang; Wei, Hongshan (Frontiers in Immunology, 2022)
Background: A preliminary study by our group revealed that the deficiency of EGF Domain Specific O-Linked N-Acetylglucosamine Transferase (EOGT) impaired regulatory T cell differentiation in autoimmune hepatitis. Nevertheless, the prognostic value of EOGT in advanced hepatocellular carcinoma (HCC) and its relationship with immune infiltration remain obscured. Methods: Initially, EOGT expression was evaluated by Oncomine, TIMER, GEO, and UALCAN databases. Besides, the prognostic potential of EOGT expression was analyzed using GEPIA, Kaplan-Meier plotter, CPTAC, Cox regression, and nomogram in HCC samples. Furthermore, we investigated the association between EOGT expression and tumor mutation burden, DNA methylation, and immune infiltration in addition to its possible mechanism via cBioPortal, TIMER, GEPIA, ESTIMATE, CIBERSORT, GSEA, STRING, and Cytoscape. Results: The expression of EOGT in HCC was significantly higher than that in normal tissues. Additionally, elevated EOGT expression was correlated with advanced tumor staging and linked to poor overall survival and relapse-free survival, serving as a significant unfavorable prognostic indicator in HCC patients. Remarkably, our results revealed that high EOGT expression subgroups with elevated TP53 or low CTNNB1 mutations have worse clinical outcomes than the others. Regarding immune infiltration, immunofluorescent staining showed that immune cells in HCC were positive for EOGT. Besides, elevated EOGT expression was linked to exhausted T cells and immune suppressor cells in HCC samples. More importantly, the proportion of CD8+ T cells was reduced in HCC samples with high level of EOGT expression, but EOGT didn’t exhibit prognostic potential in HCC samples with increased CD8+ T cells.